PENGARUH KEPERCAYAAN, HARGA, PROMOSI TERHADAP KEPUASAN PELANGGAN PENGGUNA APLIKASI SHOPEE PADA MAHASISWA STIE SEMARANG - Wati, Erlina Agustin Eka; Heridiansyah, Jefri (STIE Semarang, 2024)
This research aims to analyze the influence of Trust, Price, Promotion on Customer Satisfaction. The research method used is a quantitative method. The research results show that the Trust variable has a positive and significant effect on customer satisfaction with a t- count value of 4.656 > t-table 2.008 (sig=0.001<0.05) The Price variable has a positive and significant effect on customer satisfaction with a t-count value of 2.297 > t-table 2.008 (sig=0.003<0.05). The promotion variable has a positive and significant effect on customer satisfaction with a t-count value of 3.109 > t-table 2.008 (sig=0.003<0.05). This model is said to be feasible or fit with an F-count value of 4.947 > F-table 2.79 (sig=0.004 <0.05). The R2 value obtained is 0.739, which means that the trust, price and promotion variables have a role of 73.9% together in being able to explain or explain the Customer Satisfaction variable. Trust has a positive and significant effect on Customer Satisfaction of Shopee application users among STIE SEMARANG students. Price has a positive and significant effect on Customer Satisfaction of Shopee application users among STIE SEMARANG students. Promotion has a positive and significant effect on Customer Satisfaction of Shopee application users among STIE SEMARANG students.